The inductive research method in early Islamic tradition based on Ibn Tufayl’s Work - Hayy Ibn Yaqzan - Hashim, Rosnani; Qadous, Allam I.H.. (Revelation and Science, IIUM, 2014)
The inductive method of research has played a significant role in scientific progress throughout history. It has been proclaimed in the history of science texts that the inductive research method was first introduced by Francis Bacon (1561-1626), a western scholar. However, there are ample evidences to show that this method was earlier developed and applied by Muslim scholars about 500 years before him. For instance, Ibn-Tufayl (1100-1185), a Muslim scholar and philosopher referred to the components of the inductive research method in his well-known novel, Hayy Ibn Yaqzan (literally, Alive son of Awake). The current paper aims to explore the features of the inductive research method mooted in the aforesaid novel. The analysis showed that Muslim scientists were aware of the features of the inductive research method, and its application was evident in their works as the case demonstrated by Ibn Tufayl. Keywords: Inductive research method, Ibn Tufayl, Hayy Ibn Yaqzan, epistemology